High-intensity interval versus moderate-intensity continuous training in individuals with Parkinson's disease: Hemodynamic and functional adaptation - Fernandes, Bianca [UNESP]; Barbieri, Fabio Augusto [UNESP]; Arthuso, Fernanda Zane [UNESP]; Silva, Fabiana Araújo [UNESP]; Moretto, Gabriel Felipe [UNESP]; Imaizumi, Luis Felipe Itikawa [UNESP]; Ngomane, Awassi Yophiwa [UNESP]; Guimarães, Guilherme Veiga; Ciolac, Emmanuel Gomes [UNESP] (My University, 2020)
Purpose: To investigate the effect of high-intensity interval training (HIIT) versus moderate-intensity continuous exercise training (MICE) on hemodynamic and functional variables in individuals with Parkinson's disease. Methods: Twenty participants (13 men) were randomly assigned to a thrice-weekly HIIT (n = 12) or MICE (n = 8) for 12 weeks. Hemodynamic (resting heart rate and blood pressure, carotid femoral pulse wave velocity, endothelial reactivity, and heart rate variability) and functional variables (5-time sit-to-stand, timed up and go, and 6-min walking tests) assessed before and after training. Results: Demographic, hemodynamic and functional variables were similar between groups at baseline. Endothelial reactivity tended to increase after HIIT, but not after MICE, resulting in improved level (∼8%, P < .01) of this variable in HIIT versus MICE during follow-up. Six-minute walking test improved after HIIT (10.4 ± 3.8%, P < .05), but did not change after MICE. Sit to stand improved similarly after HIIT (27.2 ± 6.1%, P < .05) and MICE (21.5 ± 5.4%, P < .05). No significant changes were found after HIIT or MICE in any other variable assessed. Conclusion: These results suggest that exercise intensity may influence traininginduced adaptation on endothelial reactivity and aerobic capacity in individuals with Parkinson's disease.
Keywords: Aging; Cardiovascular health; Endurance training; Physical function